Teachers’ Challenges in Implementation Curriculum Merdeka by EFL Teachers’ in Mts N 1 Lubuklinggau - luthfiyyah, anggun; rahma, aan; saputra, doni; pradesta, endar; Fiani, Ani (Journal of English Education, Literature and Linguistics, 2024)
The research aims to find out what challenges are faced by English teachers at MTs N 1 Lubuklinggau to implement the Curriculum Merdeka in learning activities. This study used an interview as the instrumentation. Techniques for gathering data include observation, literature review, and interviewing and analyzing the data using descriptive qualitative methods. Research findings reveal what challenges teachers face, namely challenges in developing teaching modules, implementing Curriculum Merdeka learning, using media, classroom management, learning assessment, and Curriculum Merdeka training. Through this research, it is hoped that the findings can help English teachers cover the challenges in implementing the Curriculum Merdeka.